Evaluation Of 12 Years Of Compulsory Education Policy In Pendopo Barat District, Empat Lawang Regency, South Sumatra Province: Evaluasi Kebijakan Wajib Belajar 12 Tahun Di Kecamatan Pendopo Barat Kabupaten Empat Lawang Provinsi Sumatra Selatan - Hardiansyah, Hardiansyah; Aprianty, Henny; Noviyanto, Hernowo (JURNAL ISIP VOICE : Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
Based on Decree No. 47 of 2008 of the Government of the Republic of Indonesia concerning Compulsory Education, Article 1(1) states that "compulsory education is a minimum program that must be followed by Indonesian citizens which is the responsibility of the government and regional governments". Based on the results of observations made by researchers on Tuesday 19 December 2023 at 09.00 (Education Office of Empat Lawang District), the author found problems that emerged in the field, namely obstacles in implementing the 12 year compulsory education. Empat Lawang District Education Program. First, the level of purchasing power participation in education funding is still low. It can be said that the Intervention Stage has shortcomings in terms of planning. Because the regulations for the 12 year compulsory education program are based on the National Education System Law, program facilities are lacking due to limited student capacity, a shortage of teaching staff (Teachers) and a very limited APBD for the construction of new school units (USB). as well as renovation of school buildings which are still old buildings. The Determinant Stage can be categorized as less successful, due to the school's capacity being still inadequate, School Operational Assistance (BOS) from the central government routinely decreasing every year. The Impact Phase can be said to be successful because the HDI of Empat Lawang Regency was better in 2012, plus the percentage results of the Gross Participation Rate (APK) and Pure Participation Rate (APM) were also very high.